The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1038/s41598-018-36536-4
|View full text |Cite
|
Sign up to set email alerts
|

Randomised in situ clinical trial investigating self-assembling peptide matrix P11-4 in the prevention of artificial caries lesions

Abstract: The aim was to investigate the ability of self-assembling Peptide P11-4 Matrix (SAPM) to remineralize artificial initial caries lesions compared to the use of fluoride varnish. Volunteers were recruited for this randomised, cross-over in situ trial. Bovine specimens, half including orthodontic brackets, were recessed on the buccal aspects of mandibular appliances. Specimens included internal sound enamel control, a demineralised control and a part exposed during the in situ phase. Each phase lasted four weeks,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 43 publications
1
26
0
Order By: Relevance
“…A second publication reported an in situ trial investigating the use of a gel including SAP P 11 -4 in its matrix form (SAPM) in the prevention of demineralisation and treatment of early demineralised lesions. The results suggested that SAPM gel with 900ppm fluoride and twice a week application showed equal or superior efficacy in high risk caries patients compared to fluoride varnish 24 . P 11 -4 within the SAPM gel was developed for home treatment of caries and prevention thereof, primarily by inhibiting demineralisation, whereas the monomeric SAP P 11 -4 product for professional use was specifically developed for treatment of initial carious lesions.…”
mentioning
confidence: 95%
“…A second publication reported an in situ trial investigating the use of a gel including SAP P 11 -4 in its matrix form (SAPM) in the prevention of demineralisation and treatment of early demineralised lesions. The results suggested that SAPM gel with 900ppm fluoride and twice a week application showed equal or superior efficacy in high risk caries patients compared to fluoride varnish 24 . P 11 -4 within the SAPM gel was developed for home treatment of caries and prevention thereof, primarily by inhibiting demineralisation, whereas the monomeric SAP P 11 -4 product for professional use was specifically developed for treatment of initial carious lesions.…”
mentioning
confidence: 95%
“…The WSL persist visually almost unchanged 12-14 . Other remineralisation agents, often based on calcium phosphate, have been investigated, but could not show clinically significant advantage over fluoride 10,11,[15][16][17] .As a consequence, new treatment approaches have been called for and biomimetic mineralisation seems to be one promising possibility [18][19][20][21][22] . However, the only clinically available products at present are based on the self-assembling peptide P 11 -4 (SAP P 11 -4) 21 .The mode of action for the treatment of initial caries with SAP P 11 -4 is as follows 23,24 .…”
mentioning
confidence: 99%
“…As a consequence, new treatment approaches have been called for and biomimetic mineralisation seems to be one promising possibility [18][19][20][21][22] . However, the only clinically available products at present are based on the self-assembling peptide P 11 -4 (SAP P 11 -4) 21 .…”
mentioning
confidence: 99%
“…The evaluation was performed visually and hence the interpretation of the size reduction was subjective. Results from a randomized in-situ study demonstrated the superior remineralising effect of the self-assembling peptide compared to fluoride use on demineralised bovine enamel 28 . The applied gel contained 1,000 ppm P 11 -4 and 900 ppm fluoride, recommended for homecare prevention.…”
Section: Discussionmentioning
confidence: 98%